Environmental Knowledge and Participation in Waste Banks: Promoting Plastic Waste Reduction in Borobudur, Magelang, Central Java, Indonesia - Sutaryono; Hadi Ashar; Hastin Dyah Kusumawardani; Anas Rahmad Hidayat; Purwanti; Puji Lestari; Sukamsi; Teguh Setyaji; Dhanik Ernawati; Maria Prasasti Ragil Putri Widyaningrum; Tuti Susilowati; Heru Subaris Kasjono (Masters Program in Public Health, 2025)
Background: Public awareness of environmental health in waste management is one of the causes of government problems in waste management, especially in tourist destination areas. The behavior of carrying shopping bags is one of the efforts to reduce the volume of non organic waste. The success of this behavior has many influencing factors, so the purpose of this study is to determine the factors associated with the behavior of carrying shopping bags in Borobudur District, Magelang Regency, Central Java, Indonesia.Subjects and Method: Cross sectional analytic survey research in the Borobudur District area of 374 respondents. The time of this research was in November 2023, with a random sampling technique, and the research instrument was a questionnaire. This study analyzes six independent variables , and participants in the waste bank, on the dependent variable. We used the regression test. Logistics in the final stage.Results: High knowledge of waste management (AOR= 2.43; 95% CI= 1.04 to 5.65; p= 0.040) and participate in a waste bank (AOR= 3.27, 95% CI 1.92 to 5.58; p= 0.001) increased plastic waste reduction behavior. This study showed that there was no relationship between education, gender, occupation, and participants in the Reduce, Reuse, Recycle (TPS3R) Waste Management Site program on the shopping bag carrying behavior. Conclusion: High knowledge of waste management and participate in a waste bank increase plastic waste reduction behavior.